2018
DOI: 10.1007/s12571-018-0815-2
|View full text |Cite
|
Sign up to set email alerts
|

Food purchase patterns indicative of household food access insecurity, children’s dietary diversity and intake, and nutritional status using a newly developed and validated tool in the Peruvian Amazon

Abstract: Food security, defined as the capacity to acquire preferred food at all times, can manifest in many dimensions. Following a mixed methods approach used in India and Burkina Faso, we developed a 58-item experience-based measure in the Peruvian Amazon, based on investigator observations, relevant literature, and pre-testing with community field workers. The tool encompasses seven dimensions of food security and included measures of (1) food purchases, frequency of purchase, and location of acquisition, (2) food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 37 publications
2
28
1
Order By: Relevance
“…With the increased market orientation of agricultural production, the consumption of animal protein and fat increased, as also reported in other studies at the forest frontier in Peru, Colombia and Brazil (Piperata et al 2011;Useche and Twyman 2016;Van Vliet et al 2012), and reported as a major trend worldwide (Khoury et al 2014). Ambikapathi et al (2018) found that, in the Peruvian Amazon, sugary items, animal source food and fat intake are positively associated, as our results partially suggest. These results are extremely important, given that there is a general trend in the food and agricultural sciences to assume that increased income implies improved food security (Cruz-Garcia et al 2016), whereas our results revealed exactly the opposite trend concerning food access.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…With the increased market orientation of agricultural production, the consumption of animal protein and fat increased, as also reported in other studies at the forest frontier in Peru, Colombia and Brazil (Piperata et al 2011;Useche and Twyman 2016;Van Vliet et al 2012), and reported as a major trend worldwide (Khoury et al 2014). Ambikapathi et al (2018) found that, in the Peruvian Amazon, sugary items, animal source food and fat intake are positively associated, as our results partially suggest. These results are extremely important, given that there is a general trend in the food and agricultural sciences to assume that increased income implies improved food security (Cruz-Garcia et al 2016), whereas our results revealed exactly the opposite trend concerning food access.…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, the Peruvian Amazon has been experiencing increased flooding and drought events, with consequences for crop yields, soil erosion, water availability, and human diseases (Sherman et al 2016). These dynamics pose potential threats to food security in a region experiencing a nutrition transition where 20% of children under five suffer from chronic malnutrition (Ambikapathi et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…44 However, populations suffering from overweight or obesity also tend have a more sedentary lifestyle, 45 and a sedentary lifestyle is, in turn, associated with reduced bone mass and increased risk of other comorbidities that further prevent the adoption of exercise as preventive health behaviors. 46 In addition, although several studies have looked into child and infant nutrition status and market access in Peru, 47,48 little is known about the nutritional status and access to dietary calcium among the general population. Micronutrient deficiencies have been associated with obesity, 49 which could, in turn, contribute to the prevalence of vitamin D deficiency in overweight and obese populations.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, we measured household dietary diversity by asking about the prior day’s consumption of items within twelve food groups (grains, root vegetables, vegetables, fruits, meat, eggs, fish, legumes, dairy, fats, sugars, and other foods) ( Swindale & Bilinsky, 2006 ), and summing across all potential food categories. Finally, we asked about the number of times the household had received food as a gift in the past ( Ambikapathi et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the Peruvian Amazon, informal food sharing between households has been demonstrated to represent a key food security coping strategy. Other community-based practices intended to help households cope with economic scarcity such as parilladas (a chicken barbeque where plates are sold to neighbors, family and friends to raise money, are also common ( Ambikapathi et al, 2018 ). In this context specifically, as in other sites throughout tropical Latin America, food security, and measures of social capital and social support, have been linked to child nutritional status ( Fernández-Concha, Gilman & Gilman, 1991 ) as well as other indicators of child health ( Surkan et al, 2012 , Surkan et al, 2007 ), reinforcing the importance of these mechanisms to population health in this context.…”
Section: Introductionmentioning
confidence: 99%